Religiousness, Health, and Health Behavior in Public-Use Data of the National Center for Health Statistics - Gillum, R. F. (Journal of religion and health, 2007)
Studies of religiousness and health-related variables in large, population-based cross-sectional or, preferably, longitudinal studies, which are often prohibitively expensive, are important to complement findings from the more commonly performed studies. Inadequately known among social science researchers, the national health surveys of the Centers for Disease Control and Prevention's National Center for Health Statistics (NCHS) offer large, high-quality data sets to the public at no or nominal cost and hence offer important opportunities for research in the area of religion and health, religion and reproductive behavior, sociology of religion and psychology of religion. This report provides an overview of the data sets and a bibliography of prior research using these data, which is intended to suggest how the data of NCHS may be further exploited by researchers of religiousness and health.